Method for growing carbon nanotubes on surfaces of carbon fibers based on electroplating
By electroplating nickel catalyst on the surface of carbon fiber, the problem of time-consuming and labor-consuming and uneven distribution of the catalyst in the prior art is solved, rapid deposition of catalysts and uniform growth of carbon nanotubes are achieved, and the preparation efficiency and quality are improved.
Patent Information
- Application Number
- CN202510026506.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, during the preparation process of growing carbon nanotubes on the carbon fiber surface, it is time-consuming and labor-intensive and it is difficult to accurately control the distribution of catalyst particles.
A catalyst is deposited on the surface of the carbon fiber by electroplating, and a nickel catalytic layer is formed on the surface of the carbon fiber by electroplating nickel solution to promote the uniform growth of carbon nanotubes.
The rapid and uniform deposition of catalysts is achieved, providing a foundation for uniform growth of carbon nanotubes, and improving the preparation efficiency and quality.
Smart Images

Figure CN119591092A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon nanotube preparation, and in particular to a method for growing carbon nanotubes on the surface of carbon fiber based on electroplating. Background Art
[0002] In the prior art, in the preparation process of growing carbon nanotubes on the surface of carbon fiber, most of them are prepared by coating a catalyst solution and then reducing it. This method is time-consuming and labor-intensive, and it is difficult to accurately control the distribution of catalyst particles.
[0003] Therefore, it is necessary to provide a method for growing carbon nanotubes on the surface of carbon fiber based on electroplating to solve the above technical problems. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a method for growing carbon nanotubes on the surface of carbon fiber based on electroplating, which can deposit catalyst on the surface of carbon fiber quickly and rapidly and provide a basis for the uniform growth of carbon nanotubes.
[0005] In order to solve the above technical problems, the present invention provides a method for growing carbon nanotubes on the surface of carbon fiber based on electroplating, comprising the following steps: S1: nickel-plated carbon fiber surface; The carbon fiber is placed in a nickel electroplating solution for electroplating, and the electroplated carbon fiber is repeatedly rinsed with deionized water to remove the residual solution on the surface until the solution washed with water is neutral, and then placed in a constant temperature drying oven at 100°C for 2 hours to obtain a carbon fiber with a nickel-plated surface.
[0006] S2: Preparation of carbon nanotube / carbon fiber composites: A tubular chemical vapor deposition furnace is used to carry out in-situ growth of carbon nanotubes on carbon fibers, acetylene is used as a carbon source, argon is used as a protective gas, and a nickel coating is contained on the surface of the carbon fibers after surface pretreatment, which is used as a catalyst to promote the growth of carbon nanotubes to produce carbon nanotubes.
[0007] Preferably, the nickel electroplating solution comprises the following materials: main salt NiSO4·6H2O 270 g / L, activator NaCl 70 g / L, buffer H3BO3 40 g / L and wetting agent sodium dodecyl sulfate 0.1 g / L.
[0008] Preferably, the preparation of the nickel electroplating solution comprises the following steps: Use an electronic balance to weigh 270g of nickel sulfate hexahydrate, 70g of nickel chloride, 40g of boric acid, and 0.1g of sodium dodecyl sulfate solid medicine respectively; Use a beaker to take two cups of 500g pure water respectively, dissolve nickel sulfate hexahydrate and nickel chloride in one cup, dissolve boric acid in the other cup of pure water, and after all the solid chemicals are dissolved, stir the two cups of solution to mix evenly, then add sodium dodecyl sulfate, stir and mix thoroughly, control the pH value of the electroplating solution between 3 and 4, and you can get a nickel electroplating solution.
[0009] Preferably, in S1, the carbon fiber is placed in a nickel electroplating solution for electroplating, and specific electroplating parameters include: A DC regulated power supply is used as the power supply for electroplating, and the output mode is a constant current mode; the carbon fiber after electrochemical anodization is used as the cathode, the anode is a platinum electrode, and the electrode distance is about 10 cm; the electroplating temperature is room temperature, the current intensity is adjusted to 0.4A, the voltage is 17V~20V, and the electroplating time is controlled to be 2min.
[0010] Preferably, the step S2 specifically includes the following steps: S21: Turn on the power switch of the tube furnace to preheat the equipment, load the electroplated carbon fiber onto the quartz boat, and put it into the furnace of the tube furnace; S22: Connect the gas line, check the air tightness of the experimental equipment, and adjust the flow rate of the flow meter; S23: Set the intelligent temperature control program of the tube furnace, the heating rate is 10°C / min, and the holding time is 1h; S24: First, introduce argon gas at a flow rate of 0.6L / min to exhaust the air in the furnace, and also serve as a protective gas to prevent carbon fiber oxidation; S25: Start the temperature control program and start to increase the temperature in the furnace. After reaching the preset temperature, turn on the acetylene flow switch to introduce acetylene gas and keep the argon gas flowing continuously; S26: After reaching the set introduction time, turn off the acetylene flow switch, keep the argon gas flowing throughout the process, turn off the argon switch after the furnace is completely cooled, and take out the carbon fiber.
[0011] Preferably, in S2, during the nanotube growth process, the outlet pressures of the argon and acetylene gas flow switches are controlled at 0.1 MPa; CNTs / CF composite materials with different parameters are prepared by controlling the flow rate of acetylene gas, the growth time and the growth temperature.
[0012] Preferably, the flow rate of the flow meter is adjusted to control the flow ratio of acetylene to argon to be 0.3:0.6, in units of L / min, the carbon nanotube growth temperature is set to 500°C, and five groups of growth times are set, namely 600s, 120s, 60s, 20s, and 10s, and five sections of carbon fiber samples are put into each group each time, that is, carbon fibers that have been subjected to different electrochemical anodizing treatments and then nickel-plated, and finally a total of 25 sections of CNTs / CF composite material test samples with different growth time parameters are obtained.
[0013] Preferably, the carbon nanotube growth temperature is set to 500°C, the growth time is 1 min, and four groups of different flow ratio parameters of acetylene gas and argon gas are set, namely 0.15:0.6 L / min, 0.2:0.6 L / min, 0.3:0.6 L / min, and 0.45:0.6 L / min, respectively. Five sections of carbon fiber samples that have undergone different electrochemical anodizing treatments and then nickel-plated are placed in each group each time, and finally a total of 20 sections of CNTs / CF composite material test samples with different flow parameters are obtained.
[0014] Preferably, the flow rate ratio of acetylene to argon is adjusted to 0.3:0.6 L / min, the growth time is controlled at 1 min, and four groups of different growth temperatures are set, namely 500° C., 600° C., 700° C., and 800° C. Five sections of carbon fiber samples that have been subjected to different electrochemical anodization treatments and then nickel-plated are placed in each group each time, and finally a total of 20 sections of CNTs / CF composite material test samples with different growth temperature parameters are obtained.
[0015] Compared with the related art, the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention has the following beneficial effects: The present invention provides a method for growing carbon nanotubes on the surface of carbon fiber based on electroplating. Catalysts are deposited on the surface of carbon fiber relatively quickly and rapidly through electroplating, which can provide a basis for the uniform growth of carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The SEM images of the nickel-plated CF surface at different oxidation times in the method for growing carbon nanotubes on the carbon fiber surface based on electroplating provided by the present invention; Figure 2 XRD diagram of the electroplated carbon fiber of the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention; Figure 3 The Ni peak diagram of the XPS analysis of the nickel-plated carbon fiber according to the method for growing carbon nanotubes on the surface of the carbon fiber based on electroplating provided by the present invention; Figure 4 SEM at different growth times of the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention; Figure 5 Relative content of elements in EDS analysis of materials at different growth times in the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention; Figure 6 The Raman graph of the effect of the growth time on the CNTs / CF material in the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention; Figure 7XRD diagrams of CNTs / CF at different growth times of the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention; Figure 8 The SEM images of the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention at different growth temperatures; Fig. 9 EDS element distribution characterization diagram of the material at different growth temperatures in the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention; Fig.10 The Raman diagram of the effect of the growth temperature on the CNTs / CF material in the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention; Fig.11 XRD diagrams of CNTs / CF at different growth temperatures of the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention; Fig.12 The SEM images of the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention at different acetylene gas flow rates; Fig.13 EDS element distribution characterization diagram of the material at different acetylene gas flow rates in the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention; Fig.14 The Raman diagram of the effect of acetylene flow rate on CNTs / CF material in the method for growing carbon nanotubes on the surface of carbon fiber based on electroplating provided by the present invention; Fig.15 XRD diagram of CNTs / CF under different acetylene flow rates in the method for growing carbon nanotubes on carbon fiber surface based on electroplating provided by the present invention. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.
[0018] The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating comprises the following steps: Nickel plating on carbon fiber surface: Depositing a metal coating on the surface of carbon fiber can further activate its surface properties, improve the interfacial bonding force of the composite material, and the metal coating can also improve the conductivity and electromagnetic shielding of carbon fiber. There are two main commonly used plating methods, namely chemical plating and electroplating. Chemical plating is to evenly disperse the carbon fiber in the plating solution. Before chemical plating, the carbon fiber must first be ultrasonically activated and sensitized. The resulting coating is relatively uniform, but the coating is generally a metal compound, not a metal element. When it is subsequently composited with carbon nanotubes, a certain amount of hydrogen needs to be introduced to reduce it to a metal element. Electroplating is to use carbon fiber as the cathode, graphite or platinum as the anode, select the metal salt solution to be plated as the plating solution, and pass a certain current to form a coating on the surface of the carbon fiber. Compared with chemical plating, the coating at this time is a metal element, and no hydrogen is needed for reduction treatment, and the coating is relatively pure, and it is not easy to leave other element impurities. Overall, the development of electroplating technology is more mature, and the operation is simpler and more efficient.
[0019] Before electroplating, prepare the electroplating solution. The formula of the electroplating solution is: main salt NiSO4·6H2O 270g / L, activator NaCl 70g / L, buffer H3BO3 40g / L, wetting agent sodium dodecyl sulfate 0.1g / L. Use an electronic balance to weigh 270g of nickel sulfate hexahydrate, 70g of nickel chloride, 40g of boric acid, and 0.1g of sodium dodecyl sulfate solid medicine. Use a beaker to take two cups of 500g of pure water, dissolve nickel sulfate hexahydrate and nickel chloride in one cup, and dissolve boric acid in another cup of pure water. After all the solid medicines are dissolved, stir and mix the two cups of solution evenly, then add sodium dodecyl sulfate, stir and mix thoroughly, control the pH value of the electroplating solution between 3 and 4, and you can get the electroplating nickel solution. Use the WPS605B DC regulated power supply produced by Shenzhen Guce Electronic Technology Co., Ltd. as the power supply for electroplating, and the output mode is constant current mode. The carbon fiber after electrochemical anodization is used as the cathode, the anode is a platinum electrode, and the electrode distance is about 10cm. The electroplating temperature is room temperature, the current intensity is adjusted to 0.4A, the voltage is 17V~20V, and the electroplating time is controlled to be 2min. The electroplated carbon fiber is repeatedly rinsed with deionized water to remove the residual solution on the surface until the washed solution is neutral, and then placed in a constant temperature drying oven at 100℃ for 2h to obtain a carbon fiber with nickel plating on the surface.
[0020] Preparation of carbon nanotube / carbon fiber composites: There are many methods for the growth and preparation of carbon nanotubes, the most common ones are arc discharge, laser ablation, chemical vapor deposition, solid phase pyrolysis, glow discharge, gas combustion and polymerization synthesis. Among them, the chemical vapor deposition method is simple to operate, the carbon nanotubes grown are of high purity, and are suitable for large-scale production applications. It is mainly through the thermal decomposition of carbon-containing gases (such as methane, acetylene, ethylene, etc.) at high temperatures, which are used as carbon sources, and carbon nanotubes can be grown under the action of catalysts. By controlling the flow rate of carbon-containing gas, the temperature and time of growth, and the type and distribution of catalysts, carbon nanotubes with different morphologies can be obtained. This experiment uses the GSL1700X-80HV tubular chemical vapor deposition furnace produced by Hefei Kejing Materials Technology Co., Ltd. to carry out in-situ growth of carbon nanotubes on carbon fibers. Acetylene is used as the carbon source and argon is used as the protective gas. The surface of the carbon fiber after surface pretreatment contains a nickel coating, which is used as a catalyst to promote the growth of carbon nanotubes. The main experimental steps are as follows: (1) Turn on the power switch of the tube furnace to preheat the equipment, load the electroplated carbon fiber onto the quartz boat, and place it into the furnace of the tube furnace.
[0021] (2) Connect the gas line, check the air tightness of the experimental equipment, and adjust the flow rate of the flow meter.
[0022] (3) Set the intelligent temperature control program of the tube furnace, with a heating rate of 10°C / min and a holding time of 1 h.
[0023] (4) First, introduce argon gas at a flow rate of 0.6L / min to exhaust the air in the furnace, and at the same time serve as a protective gas to prevent carbon fiber oxidation.
[0024] (5) Start the temperature control program and begin to increase the temperature in the furnace. When the preset temperature is reached, open the acetylene flow switch, introduce acetylene gas, and keep the argon gas flowing continuously.
[0025] (6) After the set introduction time is reached, turn off the acetylene flow switch and keep the argon flowing throughout the process. After the furnace is completely cooled, turn off the argon switch and take out the carbon fiber.
[0026] During the growth process, the outlet pressure of the argon and acetylene gas flow switches were controlled at 0.1 MPa. By controlling the flow rate of acetylene gas, the growth time (the time of argon gas introduction) and the growth temperature, CNTs / CF composite materials with different parameters can be prepared. In this paper, several groups of different CNTs / CF composite materials were prepared mainly for the following parameters.
[0027] (1) Adjust the flow rate of the flow meter, control the acetylene and argon flow ratio to 0.3:0.6, in L / min, set the carbon nanotube growth temperature to 500°C, and set five groups of growth time, namely 600s, 120s, 60s, 20s, and 10s. Put five sections of carbon fiber samples into each group each time, that is, carbon fiber that has been subjected to different electrochemical anodization treatments and then nickel-plated. Finally, a total of 25 CNTs / CF composite material test samples with different growth time parameters can be obtained.
[0028] (2) The carbon nanotube growth temperature was set at 500°C, the growth time was 1 min, and four different flow ratio parameters of acetylene gas and argon gas were set, namely 0.15:0.6 L / min, 0.2:0.6 L / min, 0.3:0.6 L / min, and 0.45:0.6 L / min. Five sections of carbon fiber samples that had undergone different electrochemical anodizing treatments and then nickel-plated were placed in each group each time, and finally a total of 20 sections of CNTs / CF composite material test samples with different flow parameters were obtained.
[0029] (3) The flow rate ratio of acetylene to argon was adjusted to 0.3:0.6 L / min, the growth time was controlled at 1 min, and four different growth temperatures were set, namely 500°C, 600°C, 700°C, and 800°C. Five carbon fiber samples that had undergone different electrochemical anodizing treatments and then nickel plating were placed in each group each time. Finally, a total of 20 CNTs / CF composite material test samples with different growth temperature parameters were obtained.
[0030] (4) The CNTs / CF composites prepared under the above conditions also include samples of the effect of different electrochemical anodization times on the growth of carbon nanotubes.
[0031] When the electrochemical anodization time is 1 min, the growth time is 1 min, the growth temperature is 500°C, and the acetylene flow rate is 0.3 L / min, the diameter and length of the carbon nanotubes grown on the carbon fiber are good, the distribution is more uniform, the grown carbon nanotubes are more complete, and have fewer defects.
[0032] Finished product performance testing: Nickel plating on carbon fiber surface (1) SEM and EDS analysis of electroplated surface The surface of the electroplated carbon fiber was analyzed by SEM. Figure 1As shown in the figure, it can be seen that nickel is attached to the surface of carbon fiber, mainly in the form of spherical particles. As the electrochemical anodizing time increases, the amount of nickel attached to the surface of carbon fiber gradually increases until it completely covers the entire surface of the carbon fiber. Among them, the surface coating of the carbon fiber with an oxidation time of 1 minute is not very uniform, and some areas are not coated with nickel. The size of the nickel particles coated on the surface of the carbon fiber with an oxidation time of 2 minutes and 3 minutes is relatively consistent and the distribution is relatively uniform. When the oxidation time is 4 minutes and 5 minutes, the coating completely covers the surface of the carbon fiber.
[0033] (2) XRD analysis of electroplating surface X-ray diffraction analysis of the nickel-plated carbon fiber shows the effect of surface nickel plating. The obtained data is plotted using Origin software, and the results are as follows: Figure 2 As shown. The figure shows 5 groups of nickel-plated carbon fiber curves with electrochemical anodization time of 1min, 2min, 3min, 4min, and 5min respectively. In the figure, not only the diffraction characteristic peak representing the graphite structure of carbon fiber appears between 25° and 26°, but also the characteristic peak representing the nickel crystal structure appears, which is located at about 45° (111) crystal plane and about 52° (200) crystal plane. It shows that the carbon fiber surface is successfully plated with nickel during electroplating. At the same time, with the increase of electrochemical anodization time, this type of peak becomes sharper and the intensity is also increasing, indicating that the nickel on the surface is increasing. Analysis shows that oxidation improves the surface properties of carbon fiber, making it easier for nickel to adhere to carbon fiber.
[0034] (3) XPS analysis of electroplated surface X-ray photoelectron spectroscopy analysis of electroplated carbon fiber shows the peaks of Ni as shown in the figure below: Figure 3 As shown, it can be seen that peaks appear at binding energies of 855.8eV, 861.3eV, 873.5eV and 878.9eV. The nickel element at 855.8eV should be Ni alone or nickel in the Ni-C bond. The other three peaks should be characterized as positive divalent nickel ions, indicating that there is still a certain amount of nickel oxide or nickel hydroxide. Combined with the content analysis of each element, as the electrochemical anodization time increases, the Ni2p peak becomes higher and higher, and the content of the Ni element gradually increases, indicating that the longer the electrochemical anodization time, the more nickel is plated on the carbon fiber surface, and the easier it is to plate nickel. The analysis shows that oxidation improves the surface properties of carbon fiber, making it easier for nickel to adhere.
[0035] Performance analysis of CNTs / CF composites Effect of Growth Time on Growth of Carbon Nanotubes Scanning electron microscope and EDS spectrum analysis Scanning electron microscopy images of CNTs / CF composites prepared at growth times of 10s, 20s, 1min, 2min, and 10min under the conditions of growth temperature of 500℃, electrochemical anodization time of 1min, and acetylene gas flow rate of 0.3L / min. Figure 4 As shown in the figure, it can be observed intuitively that when the growth time is 10s, 2min, and 10min, the grown carbon nanotubes are very short and not fully grown. Especially when the growth time reaches 10min, the carbon nanotubes basically do not extend outward, but cluster together. When the growth time is 20s and 1min, the length and diameter of the carbon nanotubes observed are relatively good, and they show a tendency to extend outward.
[0036] like Figure 5 As shown in the figure, the Ni content is the highest and the C content is the lowest at 10 minutes, indicating that there are fewer carbon nanotubes grown on it, and there are still many Ni that are not covered by carbon nanotubes or many Ni that have not yet catalyzed the growth of carbon nanotubes. Among them, the C content is the highest and the Ni content is the lowest under the 20s condition, indicating that more carbon nanotubes are grown under this condition.
[0037] Raman spectroscopy analysis like Figure 6 As shown in the figure, the Raman spectra of five groups of CNTs / CF composite materials prepared by different growth times are 10s, 20s, 1min, 2min, and 10min when the anodization time is 1min, the acetylene flow rate is 0.3L / min, and the growth temperature is 500℃. It can be seen from the Raman spectrum that with the increase of growth time, the R value first increases and then decreases. The R value at 20s is the maximum value among the five groups of samples. This shows that when the growth time is 20s, the grown carbon nanotubes have fewer defects and a more complete structure.
[0038] X-ray diffraction analysis like Figure 7 As shown in the figure, the graph obtained by XRD analysis of five groups of CNTs / CF composite materials prepared by growth time of 10s, 20s, 1min, 2min, and 10min under the conditions of anodization time of 1min, acetylene flow rate of 0.3L / min, and growth temperature of 500℃. It can be seen from the figure that the characteristic peak of graphite crystal appearing between 25° and 26° changes with the change of growth time. As the growth time increases, the characteristic peak changes from flat to sharp, and then becomes flat again. The peak intensity increases first and then decreases, and the peak width decreases first and then increases. The carbon nanotube structure obtained when the growth time is 1min is the most complete and has the least defects.
[0039] Effect of Growth Temperature on Carbon Nanotube Growth Scanning electron microscope and EDS spectrum analysis like Figure 8 The following are the images obtained after SEM analysis of CNTs / CF composites prepared at different temperatures. It can be seen intuitively from the figure that at 700℃ and 800℃, there is basically no growth of carbon nanotubes or the grown carbon nanotubes are very messy. The carbon nanotubes grown at 600℃ are longer, but the growth morphology is very messy and the distribution is not uniform. The carbon nanotubes grown at 500℃ have better morphology and are more evenly distributed.
[0040] Then perform EDS spectrum analysis on the sample, such as Fig. 9 This is the EDS distribution characterization diagram of C and Ni elements on the sample surface. It can be seen from the figure that no Ni element can be detected on the surface of the composite material prepared at 600℃, 700℃ and 800℃. Combined with the SEM images of nickel-plated carbon fiber and grown carbon nanotubes, it is analyzed that at higher temperatures, the nickel coating on the surface of the carbon fiber falls off and cannot catalyze the growth of carbon nanotubes.
[0041] Raman spectroscopy analysis like Fig.10 As shown in the figure, the Raman spectra of four groups of CNTs / CF composite materials prepared at growth temperatures of 500℃, 600℃, 700℃ and 800℃ were prepared when the anodization was 1min, the growth time was 1min, and the acetylene flow rate was 0.3L / min. From 500℃ to 800℃, the R value first increased and then decreased. The maximum value among the four groups of samples was obtained at 600℃, indicating that among the four groups of growth temperatures, the carbon nanotubes grown at 600℃ have higher regularity and less surface disordered carbon atomic structure.
[0042] X-ray diffraction analysis like Fig.11 As shown in the figure, four groups of CNTs / CF composite materials were prepared at 500℃, 600℃, 700℃ and 800℃ growth temperatures when the anodization time was 1min, the growth time was 1min, and the acetylene flow rate was 0.3L / min. The XRD analysis was performed. It can be seen from the figure that the characteristic peaks characterizing graphite crystals appeared at 25° to 26°. As the temperature increases, the peak gradually changes from sharp to gentle, the peak intensity gradually decreases, and the peak width gradually increases. This shows that the growth of carbon nanotubes is affected by temperature. At 500℃, the characteristic peak of graphite crystals has the largest peak intensity and the smallest peak width, indicating that the carbon nanotubes grown under this condition have the most regular structure and the least defects.
[0043] Scanning electron microscope and EDS spectrum analysis The CNTs / CF composites prepared under different acetylene gas flow conditions were analyzed by scanning electron microscopy, and the results were as follows: Fig.12As shown in the figure, the carbon nanotubes grown under the acetylene flow rate of 0.15L / min and 0.20L / min are relatively messy and irregularly distributed. The carbon nanotubes grown under the acetylene flow rate of 0.45L / min show curling characteristics and are relatively messy in shape. The carbon nanotubes grown under the acetylene flow rate of 0.30L / min have a more regular and uniform shape.
[0044] Then perform EDS energy spectrum analysis on the material, such as Fig.13 The distribution diagram of C and Ni on the surface of the material at different flow rates shows that when the flow rate is 0.15L / min and 0.20L / min, the Ni element is basically undetectable on the surface of the material. Combined with the SEM analysis, the reason is that the surface is covered by the grown carbon nanotubes. Under the conditions of 0.30L / min and 0.45L / min, the Ni element is about 4% and 2% respectively.
[0045] Raman spectroscopy analysis like Fig.14 As shown in the figure, after Raman spectroscopy analysis of four groups of CNTs / CF composite materials prepared under different acetylene gas flow rates under the conditions of electrochemical anodization time of 1 minute, growth time of 1 minute, and growth temperature of 500°C, the obtained data was plotted using Origin. It can be seen from the figure that with the increase of acetylene flow rate, the R value first increases and then decreases. When the flow rate is 0.30L / min, the maximum value among the four groups of materials is obtained, indicating that the carbon nanotubes grown under this acetylene gas flow rate have a more complete structure and fewer defects.
[0046] X-ray diffraction analysis like Fig.15 The graph shown in Figure 1 is the spectrum obtained by XRD analysis of four groups of CNTs / CF composite materials prepared under different acetylene flow rates when the anodization time is 1 minute, the growth time is 1 minute, and the growth temperature is 500°C. It can be seen from the figure that with the continuous increase of the flow rate, the characteristic peak of the diffraction of the graphite crystal structure first gradually becomes sharp, then becomes flat, the peak intensity first increases and then decreases, and the peak width first decreases and then increases. It shows that different acetylene flow rates have an impact on the growth of carbon nanotubes. When the acetylene flow rate is 0.30L / min, the peak intensity is the largest and the peak width is the smallest, indicating that the carbon nanotubes grown under this condition have the most complete structure and the least defects.
[0047] The surface modification of carbon fiber was studied and its performance was analyzed. Then, carbon nanotube / carbon fiber composites were prepared by CVD method, and its growth parameters were studied and the performance of the composites was analyzed. The following conclusions were drawn: (1) After the carbon fiber surface is treated with electrochemical oxidation, the proportion of oxygen elements on the carbon fiber surface increases, and the number of carbon atoms containing oxygen functional groups and disordered arrangement increases. This indicates that electrochemical anodization causes the carbon fiber surface to be oxidized and has a certain etching effect on the carbon fiber. With the increase of oxidation time, this effect becomes more obvious.
[0048] (2) The electroplating of nickel on the surface of carbon fiber was studied. Scanning electron microscopy showed that the nickel coating on the surface of carbon fiber after 3 minutes of oxidation treatment was the most uniform. It was also found that the longer the oxidation time, the more nickel was coated.
[0049] (3) By controlling the parameters of anodization time, growth temperature, growth time and acetylene flow rate, different CNTs / CF composite materials were prepared by CVD method and analyzed by various methods. From the overall results: when the electrochemical anodization time is 1min, the growth time is 1min, the growth temperature is 500℃, and the acetylene flow rate is 0.3L / min, the diameter and length of the carbon nanotubes grown on the carbon fiber are good, the distribution is more uniform, the grown carbon nanotubes are more complete, and there are fewer defects.
[0050] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for growing carbon nanotubes on the surface of carbon fiber based on electroplating, characterized in that: The following steps are involved: S1: Nickel plating on carbon fiber surface: The carbon fiber is placed in a nickel electroplating solution for electroplating, and the electroplated carbon fiber is repeatedly rinsed with deionized water to remove the residual solution on the surface until the washed solution is neutral, and then placed in a constant temperature drying oven at 100°C for 2 hours to obtain a carbon fiber with a nickel plated surface; S2: Preparation of carbon nanotube / carbon fiber composites: A tubular chemical vapor deposition furnace is used to carry out in-situ growth of carbon nanotubes on carbon fibers, acetylene is used as a carbon source, argon is used as a protective gas, and a nickel coating is contained on the surface of the carbon fibers after surface pretreatment, which is used as a catalyst to promote the growth of carbon nanotubes to produce carbon nanotubes.
2. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 1, characterized in that: The nickel electroplating solution comprises the following materials: 270 g / L of main salt NiSO4·6H2O, 70 g / L of activator NaCl, 40 g / L of buffer H3BO3 and 0.1 g / L of wetting agent sodium dodecyl sulfate.
3. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 2, characterized in that: The preparation of the nickel electroplating solution comprises the following steps: Use an electronic balance to weigh 270g of nickel sulfate hexahydrate, 70g of nickel chloride, 40g of boric acid, and 0.1g of sodium dodecyl sulfate solid medicine respectively; Use a beaker to take two cups of 500g pure water respectively, dissolve nickel sulfate hexahydrate and nickel chloride in one cup, dissolve boric acid in the other cup of pure water, and after all the solid chemicals are dissolved, stir the two cups of solution to mix evenly, then add sodium dodecyl sulfate, stir and mix thoroughly, control the pH value of the electroplating solution between 3 and 4, and you can get a nickel electroplating solution.
4. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 3, characterized in that: In S1, the carbon fiber is placed in a nickel electroplating solution for electroplating, and specific electroplating parameters include: A DC regulated power supply is used as the power supply for electroplating, and the output mode is a constant current mode; the carbon fiber after electrochemical anodization is used as the cathode, the anode is a platinum electrode, and the electrode distance is about 10 cm; the electroplating temperature is room temperature, the current intensity is adjusted to 0.4A, the voltage is 17V~20V, and the electroplating time is controlled to be 2min.
5. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 1, characterized in that: The S2 specifically includes the following steps: S21: Turn on the power switch of the tube furnace to preheat the equipment, load the electroplated carbon fiber onto the quartz boat, and put it into the furnace of the tube furnace; S22: Connect the gas line, check the air tightness of the experimental equipment, and adjust the flow rate of the flow meter; S23: Set the intelligent temperature control program of the tube furnace, the heating rate is 10°C / min, and the holding time is 1h; S24: First, introduce argon gas at a flow rate of 0.6L / min to exhaust the air in the furnace, and also serve as a protective gas to prevent carbon fiber oxidation; S25: Start the temperature control program and start to increase the temperature in the furnace. After reaching the preset temperature, turn on the acetylene flow switch to introduce acetylene gas and keep the argon gas flowing continuously; S26: After reaching the set introduction time, close the acetylene flow switch, keep the argon gas flowing throughout the process, and close the argon switch after the furnace is completely cooled down, and take out the carbon fiber.
6. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 5, characterized in that: In S2, during the nanotube growth process, the outlet pressures of the argon and acetylene gas flow switches are controlled at 0.1 MPa; CNTs / CF composite materials with different parameters are prepared by controlling the flow rate of acetylene gas, the growth time and the growth temperature.
7. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 6, characterized in that: The flow rate of the flow meter was adjusted to control the flow ratio of acetylene to argon to be 0.3:0.6, in L / min. The carbon nanotube growth temperature was set to 500°C, and five groups of growth times were set, namely 600s, 120s, 60s, 20s, and 10s. Five sections of carbon fiber samples were put into each group each time, that is, carbon fibers that had been subjected to different electrochemical anodizing treatments and then nickel-plated. Finally, a total of 25 CNTs / CF composite material test samples with different growth time parameters were obtained.
8. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 6, characterized in that: The carbon nanotube growth temperature was set at 500°C, the growth time was 1 min, and four groups of different flow ratio parameters of acetylene gas and argon gas were set, namely 0.15:0.6 L / min, 0.2:0.6 L / min, 0.3:0.6 L / min, and 0.45:0.6 L / min. Five sections of carbon fiber samples that had undergone different electrochemical anodizing treatments and then were nickel-plated were put into each group each time, and finally a total of 20 sections of CNTs / CF composite material test samples with different flow parameters were obtained.
9. The method for growing carbon nanotubes on the surface of carbon fiber based on electroplating according to claim 6, characterized in that: The flow ratio of acetylene to argon was adjusted to 0.3:0.6 L / min, the growth time was controlled at 1 min, and four groups of different growth temperatures were set, namely 500°C, 600°C, 700°C, and 800°C. Five sections of carbon fiber samples that had undergone different electrochemical anodizing treatments and then nickel-plated were placed in each group each time. Finally, a total of 20 CNTs / CF composite material test samples with different growth temperature parameters were obtained.
Citation Information
Patent Citations
Method for preparing nano carbon fiber
CN101177803A
Carbon nanotube-transition metal-carbon fiber composite material and preparation method and application therefor
CN105375041A
Electrode material of flexible super capacitor of carbon fiber / carbon nanotube and preparation of electrode material
CN106971859A